2019
DOI: 10.1016/j.jpcs.2019.02.031
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical investigation of superconductivity mechanism in the filled skutterudites YRu4P12, YOs4P12, LaOs1P12 and LaOs4As12

Abstract: We have investigated the structural, electronic, phonon and electron-phonon interaction properties of the filled skutterudites YRu 4 P 12 , YOs 4 P 12 , LaOs 4 P 12 and LaOs 4 As 12 by utilizing the generalized gradient approximation of the density functional theory. It is found that the electronic states close to the Fermi energy are heavily contributed by the transition metal and pnictogen atoms, while the contribution of the filler atom (Y or La) to the occupied bands is negligible. Our electron-phonon calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…The heavier atoms contribute to the low frequency mode in skutterudites, which are consistent with the result reported in Y-based skutterudites. 61…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The heavier atoms contribute to the low frequency mode in skutterudites, which are consistent with the result reported in Y-based skutterudites. 61…”
Section: Resultsmentioning
confidence: 99%
“…The heavier atoms contribute to the low frequency mode in skutterudites, which are consistent with the result reported in Y-based skutterudites. 61 When constituent atoms oscillate out of phase in their crystal lattice, it gives rise to the optical phonon modes. One can note flat and dense optical modes in higher frequency of CeFe 4 P 12 as compared to other due to the vibration of the lowest mass of P among the constituent atoms.…”
Section: B Dynamic Propertiesmentioning
confidence: 99%
“…Shirotani et al have reported YFe 4 P 12 , YRu 4 P 12 , and YOs 4 P 12 compounds which show superconductivity below critical temperature (T c ) of 7 K, 8.5 K, and 3 K, respectively [2][3][4]. Uzunok et al confirmed the validity of T c in YT 4 P 12 (T = Ru or Os) by utilizing the generalized gradient approximation of the density functional theory [5]. Hence, we have reported experimental results on pressure dependence of T c of both YFe 4 P 12 and YOs 4 P 12 [6,7] compounds and YFe 4 P 12 reveals positive pressure coefficient (dT c /dP ∼ 1 K/GPa) whereas YOs 4 P 12 shows negative pressure coefficient (dT c /dP ∼ -0.1 K/GPa).…”
Section: Introductionmentioning
confidence: 99%